Parent Support for School Well-Being in Students During the Covid-19 Pandemic - Aziza Fitriah; Rizky Amalia Aprianty (Universitas Muhammadiyah Banjarmasin, 2021)
At the beginning of 2020, the whole world was faced with a global pandemic, namely the emergence of the Covid-19 virus which changed all systems of life, including the world of education. All lectures turned into online media, namely distance lectures, where in the process there were many obstacles and challenges that students had to face. In this condition, to continue to realize prosperity in the learning process, students are required to harmonize themselves which has a sufficient impact on welfare in learning, namely school well-being. Learning from home with all kinds of conditions faced by students, parental support is important to help realize school well-being in the distance learning process. The purpose of this study was to find out how the relationship between parental support and school well-being in students during the Covid-19 pandemic. The method used is quantitative to determine the relationship between variable X and Variable Y. Variable X is Parental Support, and variable Y is School Well-Being. The instrument used in this study there are 2 measurement scales for variable X, namely the Parental Support scale and the instrument variable Y, namely the School well-being behavior scale. The target population to be studied are undergraduate psychology students at the Muhammadiyah University of Banjarmasin. that there is a significant positive relationship between Parental Support for School Well Being for Students during the Covid-19 pandemic, with a figure of 0.379 with p = < 0.000. The strength of the influence of Parental Support on School Well Being is 14.4%. this means that other variables that affect 85.6%.